Effect of Various Roofing Materials on Physiological Response of Osmanabadi Kids (Indian Journal of Animal Production and Management, 2024)
The present study was carried out at  Osmanabadi goat unit of Red Kandhari Research  and Instructional Farm, College of Veterinary and  Animal Sciences, Parbhani, MAFSU, for a period of  90 days. Eighteen Osmanabadi kids were divided  into three treatment groups viz T0 (Thatch roof) T1  (Asbestos roof) T2 (FRP sheet roof). The variation  in weekly pulse rate, respiration rate and body  temperature were recorded in the morning and  evening throughout the experiment. The results  revealed that the thatch roof shed significantly  (P
Keywords: Osmanabadi kids; Body weight; thatch roof; asbestos roof; fibre reinforced plastic (FRP) sheet